Main synoptic conditions over India and neighbourhood during a period of 40 days before onset of monsoon 1979 (MAUSAM, 1980)
The position of lows, highs, troughs and ridges have been studied in the lower and upper troposphere with respect to their normal positions during the 40 days period before the onset of monsoon in 1979. The unfavourable effects of some of these features have also been studied in respect of the onset on monsoon during 1979.